Metabolomics profiling reveals berberine-inhibited inflammatory response in human gingival fibroblasts by regulating the LPS-induced apoptosis signaling pathway - Zhang, Ying; Guo, Yanyang; Wei, Wenjia; Zhang, Zhongxiao; Xu, Xiaodong (Frontiers in Pharmacology, 2022)
In this article, we examined the Berberine's biological effects and molecular mechanisms with inflammatory response model induced by lipopolysaccharide in human gingival fibroblasts (HGFs) using metabolomics. The viability of HGFs was determined by using the Cell-Counting Kit-8 (CCK8). ELISA was used to measure inflammatory cytokines, including interleukin (IL)-6, IL-1β and tumor necrosis factor- α (TNF-α). An investigation of Western blots was conducted to investigate the related protein of apoptosis. Low concentrations of berberine (0.1, 0.5, and 1 µmol·L-1) did not affect HGF growth, whereas high concentrations of berberine (5-25 µmol·L-1) significantly activated cell proliferation. Berberine suppressed the elevated secretion of IL-6, IL-1β and TNF-α expression levels induced by LPS in HGF. Western blot analysis showed that 10µmol·L-1 of berberine significantly inhibited LPS-induced apoptosis signaling pathway activation. Our results suggested that Berberine HGFs Cells against LPS-Induced Apoptosis and production of pro-inflammatory mediators. Berberine maybe a potential therapeutic drug for the management of periodontitis.